Hollow GdPO4:Eu3+ microspheres: Luminescent properties and applications as drug carrier. (April 2016) - Tang, Yanxia; Mei, Rui; Yang, Shaokun; Tang, Hongxia; Yin, Wenzhong; Xu, Yongchun; Gao, Yaping
Abstract: GdPO4 :Eu 3+ samples were synthesized by a hydrothermal process using melamine formaldehyde (MF) as template. The X-ray diffraction (XRD) patterns and the Fourier Transform Infrared (FTIR) spectrum suggested that GdPO4 :Eu 3+ has a hexagonal phase. The scanning electron microscope (SEM) and transmission electron microscope (TEM) images showed that the obtained GdPO4 :Eu 3+ are hollow microspheres with diameters in the range of 1–1.5 μm. Under the excitation at 245 nm, hexagonal GdPO4 :Eu 3+ hollow microspheres showed emission bands originating from the 5 D0 → 7 FJ (J = 1, 2, 3 and 4) transitions of Eu 3+ . The drug release properties of hexagonal GdPO4 :Eu 3+ hollow microspheres were exhibited by the doxorubicin hydrochloride (DOX) release test. The biocompatibility of hexagonal GdPO4 :Eu 3+ hollow microsphere was tested by the standard 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. The results indicated that hollow GdPO4 :Eu 3+ microspheres have potential applications in biomedicine fields. Highlights: Synthesis of hexagonal GdPO4 :Eu 3+ hollow microspheres. Orange-red color light of hexagonal GdPO4 :Eu 3+ hollow microspheres. Release property of 77% at the pH value of 6 for GdPO4 :Eu 3+ hollow microspheres. Promising use in biomedical field for GdPO4 :Eu 3+ hollow microspheres.